‘Levodopa Phobia’: a review of a not uncommon and consequential phenomenon - Titova, Nataliya (NPJ Parkinsons Dis, 2018)
‘Levodopa Phobia’ is under-recognised in Parkinson’s disease but can cause profound detrimental clinical complications if left to continue. Several types can be encountered in clinical practice and can be driven by a misplaced fear of levodopa-induced dyskinesias, other gastrointestinal side effects and also the theoretical notion that levodopa may be toxic to dopaminergic neurons in the brain. The condition can be underpinned by a sense of strong influence from the physicians or carers who are unwilling to prescribe or consider levodopa, and also high levels of anxiety or even impulsive compulsive traits in patients who have been influenced by available literature or social media-based information. If unrecognised, the clinical issue may lead to motor deterioration and related muscle contractures leading to social isolation as well as a range of non-motor symptoms. In some, there may be emergence of intrusive impulse control disorders because of reliance on only dopamine agonists related to the fear of taking levodopa. Four cases illustrate the different patterns of ‘Levodopa Phobia’ in this study. Management of levodopa phobia is complex and includes recognition and skilled neuropsychological interventions to break the misperceptions about the complications of levodopa therapy.